Development of Interactive Folklore Based on Android Oriented to Local Wisdom to Improve Reading Comprehension of Elementary School Students - Karimatus Saidah; Rian Damariswara (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractThe aims of this research are 1) to describe the process of developing interactive multimedia based on android on fairy tale material for grade 3 elementary school students based on the Rowntree development model; 2) knowing the validity of the product; 3) knowing the practicality of the product being developed. The type of research used was research and development. The development model used was the Rowntree model. This research produced interactive folklore based on android applications. The instruments used in this research were validation questionnaires and sheets for comments and suggestions from the validator. This research produced the interactive folklore based on android applications. The folklore presented was based on the local wisdom of East Java. The folklore application was equipped with games of language to improve the students' ability to understand folklore material. The folklore application was validated by multimedia experts and language learning experts with a product validity level of 85.5%. The results of the practicality questionnaire showed a combined average score of 93.3%. The advantages of the folklore application developed are that the material is packaged in a simple and attractive way, contains language games, and can be opened using a smartphone. However, the weakness of the product is that the command sentences in the quiz are less specific, and there is no discussion in the game. In addition, it can only be opened using a smartphone.Keywords: reading comprehension, folklore, android application.Â AbstrakTujuan penelitian ini adalah 1) mendeskripsikan proses pengembangan multimedia interaktif berbasis android pada materi dongeng bagi siswa kelas 3 sekolah dasar berdasarkan model pengembangan Rowntree; 2) mengetahui kevalidan produk; 3) mengetahui kepraktisan produk yang dikembangkan. Jenis penelitian yang digunakan adalah penelitian dan pengembangan model rownthree. Instrumen yang digunakan dalam kegiatan penelitian ini adalah angket validasi dan lembar pengisian komentar dan saran validator. Penelitian ini menghasilkan dongeng interaktif berbasis aplikasi android. Dongeng yang disajikan merupakan dongeng-dongeng sesuai dengan kearifan lokal Jawa Timur. Aplikasi dongeng dilengkapi dengan permainan bahasa untuk meningkatkan kemampuan siswa dalam memahami materi dongeng. Aplikasi dongeng telah divalidasi oleh ahli multimedia dan ahli pembelajaran bahasa dengan tingkat validitas produk sebesar 85,5%. Sedangkan hasil angket kepraktisan menunjukkan skor rata-rata gabungan sebesar 93,3%. Kelebihan dari aplikasi dongeng yang dikembangkan adalah materi dikemas sederhana dan menarik, memuat permainan bahasa, serta dapat dibuka menggunakan smartphone secara offline. Sedangkan kekurangan produk yaitu kalimat perintah dalam kuis kurang spesifik dan tidak ada pembahasan dalam permainan. Selain itu, produk hanya dapat dibuka menggunakan smartphone.Kata kunci: pemahaman membaca, cerita rakyat, aplikasi android.